The Effect Of Giving Calcium As An Effort To Prevent Preeclampsia: A Literature Review - Cahyani, Desy Dwi Cahyani; Ayundasari, Ega; Mardiana, Heppy Rina; Sunaeni, Sunaeni; Mulyati, Mulyati; Irawati , Irawati (PT.Mantaya Idea Batara, 2023)
Preeclampsia is a pregnancy disorder accompanied by hypertension and proteinuria. Efforts to prevent preeclampsia can be made with medical prevention, namely, meeting the calcium needs of pregnant women. This research aims to determine the effect of givingcalcium to prevent preeclampsia. The method used in the literature review is a systematic mapping study obtained from 3 databases, namely Pubmed, Garuda, and Google Scholar, using inclusion and exclusion criteria. Key term used in searching literature: